2020
DOI: 10.1088/1361-6463/abb488
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the correlation between perpendicular magnetic anisotropy, spin mixing conductance and interfacial Dzyaloshinskii–Moriya interaction in CoFeB-based systems

Abstract: Correlation between interfacial Dzyaloshinskii–Moriya interaction (iDMI), perpendicular magnetic anisotropy (PMA) and spin pumping-induced damping was investigated in CoFeB-based systems grown by sputtering on Si substrates, using Pt, Ta, Cu, W and MgO capping layers. Vibrating sample magnetometer, Brillouin light scattering (BLS) and broadband ferromagnetic resonance techniques were combined for this aim. The CoFeB thickness dependence of iDMI and PMA constants, in CoFeB/X (where X = Pt, Cu/Pt, Ta/Pt or W/Al)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The reported chirality for various stacks are summarized in Table 1, together with the method of measurement. For instance, in similar Ta/FeCoB/MgO stacks, opposite DMI signs and domain wall chiralities are found by different teams [38], [39], [32], a variation of MgO thickness in Ta/FeCoB/MgO/Pt samples lead to an inversion of DMI sign [40] and the insertion of an ultrathin Ta layer at the FeCoB/MgO interface gives a right-handed chirality, as shown in the supplementary materials of [41]. Similarly, in Ta/FeCoB/TaOx stracks, either left-of right-handed chiralities have been observed [10], [42], [43], [44], [45] .…”
Section: Introductionmentioning
confidence: 99%
“…The reported chirality for various stacks are summarized in Table 1, together with the method of measurement. For instance, in similar Ta/FeCoB/MgO stacks, opposite DMI signs and domain wall chiralities are found by different teams [38], [39], [32], a variation of MgO thickness in Ta/FeCoB/MgO/Pt samples lead to an inversion of DMI sign [40] and the insertion of an ultrathin Ta layer at the FeCoB/MgO interface gives a right-handed chirality, as shown in the supplementary materials of [41]. Similarly, in Ta/FeCoB/TaOx stracks, either left-of right-handed chiralities have been observed [10], [42], [43], [44], [45] .…”
Section: Introductionmentioning
confidence: 99%
“…The other method for this correlation investigation is to vary the thickness of the HM layer [11]. Systems based on the insertion of an ultrathin metallic or nonmetallic interlayer (dusting layer) of variable thickness, at the interface the between FM layer and Pt as the HM [12], have also been used for such investigation. Here, Pt is used as the HM since it is known to be the HM with the strongest iDMI.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Pt is used as the HM since it is known to be the HM with the strongest iDMI. The authors have observed a linear dependence between iDMI and PMA constants and have concluded they are strongly correlated as interface effects that have a SOC-related physical origin [11,12]. Other authors such as Zhu et al [13] have used composition variation in Au 1−x Pt x /Co [10] or Pd 1−x Pt x [14] interfaces to significantly tune the iDMI and PMA.…”
Section: Introductionmentioning
confidence: 99%
“…2.6 [145]. The following material parameter values, typical of Oxide/CoFeB/HM multilayers [146][147][148][149][150], were used in the micromagnetic simulations: A ex = 20 pJ m −1 (exchange stiffness), M s = 1 MA m −1 (saturation magnetization), K u = 0.8 MJ m −3 (uniaxial anisotropy), D = 1.8 mJ m −2 (interfacial Dzyaloshinskii-Moriya), λ s = 3.7 × 10 −5 (magnetostriction), α = 0.3 (damping constants), and θ sh = −0.33 (spin Hall angle). Fig.…”
Section: Strain-control Of the Skyrmion Hall Effectmentioning
confidence: 99%